On efficient CUSUM-type location control charts using auxiliary information. Issue 1 (2nd January 2018) - Sanusi, Ridwan A.; Abbas, Nasir; Riaz, Muhammad
Abstract: Statistical quality control deals with controlling and monitoring of production/manufacturing processes for improved quality of products. Control charts are the major tools that are widely applied in industry to keep the process variability under control. One of the most popular categories of control charts is CUSUM chart which is memory chart. It is based on utilizing the information on cumulative sum pattern. This article proposes a new structure for CUSUM charts based on the utilization of auxiliary information using different estimators. We have used a variety of performance measures including average run length, Extra Quadratic Loss, Ratio of Average Run Lengths and Performance Comparison Index. These performance measures of the proposed chart are evaluated in terms of varying shifts in study variable and are compared with some existing control structures meant for the same purposes. The comparisons revealed that the proposed charts perform very well relative to the other competing charts under discussion. A real life industrial example is also provided to demonstrate the application procedure of the proposals of this study.